Ecological Risks of Heavy Metals and Microbiome Taxonomic Profile of a Freshwater Stream Receiving Wastewater of Textile Industry - Odubanjo, Grace Olunike; Oyetibo, Ganiyu Oladunjoye; Ilori, Matthew Olusoji (Frontiers in Environmental Science, 2021)
Textile wastewater (TWW) contains toxic metals that are inimical to microbiome, aesthetic quality and health of the receiving freshwater. TWW-impacted freshwater (L2) was assessed for metals eco-toxicity and consequent impact on microbiome taxonomic profile (MTP) compared to pristine environment (L1). The conductivity (1750 µS/cm), chemical oxygen demand (2110 mg/l), biochemical oxygen demand (850 mg/l) and salinity (5250 mg/l) of L2 were far above the permissible limits. Mercury posed very high ecological risks in the water column of L2 as lead, arsenic, and copper exerted high risk in the sediment. MTP of L2 revealed dominance of Euryarchaeota (48.6%) and Bathyarchaeota (45.9%) among the Archaea. Relative abundances of Proteobacteria and Bacteroidetes increased from 38.3% and 2.0%, respectively, in L1 ecosystem to 42.1% and 12.9%, correspondingly, in L2. Unclassified Eukarya_uc_p (50.4%) and Fungi_uc (16.0%) were key players among the fungi kingdom in L2. Impact of the TWW on the microbiome was evident with the extinction of 6249, 32272, and 10029 species of archaea, bacteria and fungi, respectively. Whereas, 35157, 32394, and 7291 species of archaea, bacteria and fungi, correspondingly, exclusively found in L2 were assumed to be invading resident community that combined with dominant autochthonous strains in shaping the ecophysiology dynamics in TWW-impacted freshwater. While the sensitive microorganisms of in L2 are suggested bio-indicators of TWW ecotoxicity, the emergent and dominant taxa are pivotal to natural attenuation processes in the contaminated ecosystem that would be adopted for biotechnological strategy in decommissioning the TWW-impacted freshwater.